EL LIDERAZGO Y SU IMPLICANCIA EN LA GESTIÓN INTEGRADA DE CLIENTES Y SERVICIOS EN TELEFÓNICA DEL PERÚ - Acuña Oré, Pepe (2010)
This research, referred to the implications of leadership in integrated customer management and services, was carried out in Telefónica del Perú, between July 2008 and April 2010. The purpose of this research was to determine the way the managerial leadership helps to improve the performance of integrated management. Participated in this research, first, all areas of Telefónica del Perú and its subsidiary, Telefónica Empresas, and secondly, a representative group of TOP clients, who are called preferred customers, from different economic sectors. This study has practical value for Telefónica del Perú, therefore, to identify leadership styles that contribute to increased customer satisfaction, will be valuable information for loyalty thereby achieving higher profits. Of the various theories, it was considered Path-Goal Leadership theory, for its applicability to the flexible and dynamic nature of the activities in Telefónica del Perú. Data analysis revealed that the leaders and workers demonstrated self-control and self-motivated process, have clear what is expected of them and feel able to make their own decisions, that a high percentage of chiefs (86%), have the achievement-oriented leadership and that within this group, who have participative style, have better influence to employees satisfaction, determining a work environment conducive to the development of activities. Also, having found an association between managers’ leadership styles and little solidarity, with a low rate of satisfaction with the work environment, it is recommended that Telefónica del Perú creates awareness programs and / or training to managers on issues of leadership. It was also found that the achievement-oriented leadership style, generate greater customer satisfaction.